Wokół genezy Zawiszy Czarnego Juliusza Słowackiego w świetle korespondencji poety oraz jego bliskich - Jakub Rawski (Zagadnienia Rodzajów Literackich, 2021)
Juliusz Słowacki’s drama Zawisza Czarny [Zawisza the Black] is one of the poet’s least described and analysed works. This drama is one of the last literary texts of the poet (next to Samuel Zborowski from 1845), written in 1844–1845. The researchers included it in the socalled “Mystical period” of the work of the poet. It seems that it is still worth asking about the genesis of a literary work, as it is, after all, an immanent part of the history of literature. The article outlines the hypothetical provenance of drama Zawisza Czarny, with particular attention to the biographical context. As the basis for conclusions and assumptions the selected correspondence of the poet to his mother, Salomea Bécu and his friend Joanna Bobrowa. Letters of Zygmunt Krasiński in which he mentioned Słowacki at the time when he was probably working on Zawisza Czarny and later, when writing was completed. The research problems discussed in the text concern: the possible causes of the work, the conditions in which the drama was created, the potential inspiration of the bard and the reconstruction of the biographical context. Considering the work in question in terms of biography is only an interpretative proposal, a set of conjectures and possible references.